2023
DOI: 10.1097/brs.0000000000004619
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Subsidence and Its Clinical Impact Following Expandable Cage Insertion in Minimally Invasive Transforaminal Interbody Fusion

Abstract: Study Design. Retrospective review of prospectively collected multisurgeon data. Objective. Examine the rate, clinical impact, and predictors of subsidence after expandable minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) cage. Summary of Background Data. Expandable cage technology has been adopted in MI-TLIF to reduce the risks and optimize outcomes. Although subsidence is of particular concern when using expandable technology as the force required to expand the cage can weaken the endplate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…For example, Smith et al reported patient satisfaction following outpatient lumbar fusion surgery to be 92%, 32 with other similar studies demonstrating satisfaction rates upwards of 80% 33 . These results are well in line with existing literature on satisfaction following inpatient lumbar fusion 36–40 . This is maybe unsurprising, but our systematic review reinforces the idea that lumbar fusion surgery can be performed effectively, with high-quality PROMs and satisfaction even in the outpatient setting.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, Smith et al reported patient satisfaction following outpatient lumbar fusion surgery to be 92%, 32 with other similar studies demonstrating satisfaction rates upwards of 80% 33 . These results are well in line with existing literature on satisfaction following inpatient lumbar fusion 36–40 . This is maybe unsurprising, but our systematic review reinforces the idea that lumbar fusion surgery can be performed effectively, with high-quality PROMs and satisfaction even in the outpatient setting.…”
Section: Discussionsupporting
confidence: 89%
“…33 These results are well in line with existing literature on satisfaction following inpatient lumbar fusion. [36][37][38][39][40] This is maybe unsurprising, but our systematic review reinforces the idea that lumbar fusion surgery can be performed effectively, with high-quality PROMs and satisfaction even in the outpatient setting.…”
Section: Literature Reviewsupporting
confidence: 54%
“…Patients were split up into two cohorts based on the intraoperative modality: robotics (ExcelsiusGPS, Globus Medical Inc., Audubon, PA) and navigation (Stryker SpineMask, Stryker Corp., Kalamazoo, MI). The robotics and navigation workflows 12,13,15,16 and the MI-TLIF technique [17][18][19][20][21][22] were utilized, as previously described in the literature by our group.…”
Section: Methods Study Design and Patient Selectionmentioning
confidence: 99%
“…Using TikTok’s search algorithm, we selected a sample of 50 videos for each hashtag utilized, including “#spinalfusion,” “#scoliosissurgery,” and “#spinaldecompression.” These hashtags were chosen as they provided a representative sample of spine surgery [ 9 - 17 ]. The 3 hashtags additionally had the most views of spine surgery hashtags and thus provide a good sample of content available on TikTok.…”
Section: Methodsmentioning
confidence: 99%
“…These hashtags were chosen as they provided a representative sample of spine surgery. [9][10][11][12][13][14][15][16][17] The 3 hashtags additionally had the most views of spine surgery hashtags and thus provide a good sample of content available on TikTok. Videos were excluded if they had less than 1,000 views, were duplicates, non-English language, and if they lacked audio or visual content.…”
Section: Video Selection and Data Collectionmentioning
confidence: 99%